(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study is on impact of the use of Guided discovery teaching method under individualized and group learning conditions on secondary students’ retention in trigonometry in Katsina Zonal Quality Assurance in Katsina State. The research adopted Quasi-experimental pre-test post-test control group design. Data were collected from a sample of 172 students comprising 95 boys and 77 girls from three randomly selected public schools in in Katsina Zonal Quality Assurance in Katsina State. The schools were grouped into experimental and control group. A 25 item instrument called Trigonometry Performance Test (TPT) were adopted from past WAEC, NECO and JAMB questions on Trigonometry with a reliability coefficient of 0.832 using Pearson Product Moment Correlation statistics with the aid of SPSS Package 21.0 version. The TPT was administered twice, before experiment (Pre) and two weeks after experiment (Post post test). Data collected were analyzed using descriptive statistics of mean and standard deviation for answering the research questions and One way ANOVA at coefficient alpha level of 0.05 for testing the hypotheses. Findings of the study are; there is significant difference between the retention mean performance scores of students taught trigonometry using guided discovery method with individualized learning strategy, guided discovery method with group learning strategy and lecture method. There is no significant difference in retention of male and female students taught trigonometry using guided discovery method with individualized learning and guided discovery method with group learning. It was recommended that Guide discovery either as individualized or group should be incorporated among instructional methods for teaching mathematics and teachers in training should be equipped with knowledge vast enough to implement guided discovery methods of teaching mathematics.